Toward a comparison of DNA profiling and databases in the United States and England - Goulka, Jeremiah E. (Technical report (Rand Corporation), 2010)
RAND researchers explored the U.S. and English forensic DNA analysis systems to find out whether England has capitalized more fully on their crime-fighting potential than the U.S. system.